SCHOOL STRATEGY IN INCREASE SUPERIORITY GRADUATES ENTER HIGHER EDUCATION (Study at SMA Negeri 1 Perbaungan) - Pangaribuan, Sardora; Pratiwi, Sri Nurabdiah; Amiruddin, Amiruddin (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This research aims to know the School Strategy to Increase ExcellenceGraduates Enter Higher Education at SMA Negeri 1 Perbaungan.in Thisresearch is a researcher using a qualitative approach to the type ofapproach analysis qualitative. Collected data that is by using observationtechniques, interviews, and documentation. Data analysis uses the Milesand Huberman model, namely data reduction, data presentation, anddrawing conclusions. Checking the validity of the data by extendingobservations, triangulation, and using references. From the results of thisstudy obtained that school strategy in m Increasing the excellence ofgraduates starting from the school's commitment to improving quality,then followed by an increase in resources / Professionalism teachers andeducation personnel, improvement of infrastructure, improvement ofstrong principal management. Strategy in improving the quality of thesegraduates requires the involvement of all elements of the organization,starting from the principal, teachers, staff school,student.Apart from that,parties related externals such as parents/guardians of students, government,community, and existing stakeholders.Keywords: Strategy, Excellence, Graduate